School-based Prevention of Mosquito-borne Diseases: A Systematic Review - Emilia Chandra; Sukmal Fahri; Asni Johari; Syaiful Syaiful (Iran University of Medical Sciences, 2023)
Background: Mosquito-borne diseases (MBDs) are among the important and highly complex issues in public health. School age children have been encouraged to participate in ongoing household MBDs control activities such as source reduction, as part of MBDs control efforts. Numerous school-based health education studies have been conducted worldwide on the interventions to prevent MBDs. However, the results are still varied and uncertain. This systematic review aims to answer the question of:" Are school-based educational programs able to improve students' knowledge, attitudes, and practices about mosquito-borne diseases?". Methods: This systematic review was conducted using the Preferred Reporting Items for systematic reviews and meta-analyses (PRISMA) statement. A systematic literature search was performed using Sciencedirect, Cochrane library, PubMed, ProQuest, and the Wiley Online Library in the time period of 2000 to 2021. Eligibility criteria was determined according to PICOS guidelines. Quality and risk of bias of the studies were assessed by the effective public health practice project tool (EPHPP) and Cochrane risk-of-bias tool (RoB-2), respectively. Data were analyzed qualitatively, by looking at the number of participants, study design, and the main results obtained in each of the included studies. Results: In the initial search, 1,424 studies were found. Duplicates, those not relevant to students and MBDs, review articles, case reports, dissertations and non-English articles were eliminated. Twenty-three studies fulfilling the inclusion criteria were analyzed. Overall, there was an increase in knowledge, attitude, and practice regarding MBSs. However, knowledge appears to be the most important variable targeted by the included studies. All studies stated a significant increase in knowledge. Conclusion: The effect of the educational interventions on knowledge was more prominent. Future studies need more specialized educational interventions to have a stronger impact on students' attitudes and performance. Further research is also needed to generate stronger evidence and evaluate the long-term impact of these interventions on students' knowledge, attitudes, and practice. The results of this review can be a guide to carry out appropriate interventions in elementary schools.